The Ritual Lament in Greek Tradition - Yatromanolakis, Dimitrios; Roilos, Panagiotis (Rowman & Littlefield Publishers, 2002)
Margaret Alexiou's The Ritual Lament in Greek Tradition, first published in 1974, has long since been established as a classic in several fields. This is the only generic and diachronic study of learned and popular lament and its socio-cultural contexts throughout Greek tradition in which a great diversity of sources are integrated to offer a comprehensive and penetrating synthesis. Its interdisciplinary orientation and broad scope have rendered The Ritual Lament in Greek Tradition an indispensable reference work for classicists, byzantinists, neohellenists, folklorists, and anthropologists. Now a second edition, revised by Dimitrios Yatromanolakis and Panagiotis Roilos, has been made available. This new edition also includes a valuable up-to-date bibliography on ritual lament and death in Greek culture.